Owner's Responsibility of Traffic Vehicles With E-Ticketing - Fandy Firmansyah; Evi Retno Wulan (Faculty of Law, Merdeka University Surabaya, Indonesia, 2021)
The e-ticket system or electronic ticketing has been piloted in several big cities. This electronic ticket, which is commonly called e-ticket, is a digitalization of the ticket process, by utilizing technology it is hoped that the entire ticketing process will be more efficient and effective and can also help the police in administrative management. However, in this e-ticket there are weaknesses as a result of which injustice arises. This study aims to determine whether the vehicle owner is responsible for violations committed by other parties and to find out what efforts the vehicle owner can make with E-Tilang. Based on the problems discussed in this thesis, the research method used is the legal research method with the statue approach and conceptual approach, the type of data uses primary legal material and secondary legal material, the data collection method used is through literature study and legal materials. The results of the study indicate that e-ticketing in the framework of criminal law is more focused on criminal responsibility and vehicle owners are not responsible for violations committed by other parties in the practice of implementing the Article in Law Number 22 Year 2009 concerning Traffic and Road Transportation. Efforts that can be made by vehicle owners are to protest to the police if the photo captured by CCTV is not him.